ANALISIS KERAWANAN DAN KEJADIAN LONGSOR PADA SUB DAS BAKAR DAS TABUNIO - Meigi Sugihanli; Badaruddin Badaruddin; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2024)
Landslide is the displacement of slope-forming material in the form of rock, debris, soil, or mixed materials, moving down or off the slope. The decrease in the carrying capacity of the watershed is one of the factors in the occurrence of landslides. The purpose of this study was to analyze the level of landslide vulnerability and validate the level of landslide vulnerability based on actual land use in the Tabunio Watershed area, the Bakar Sub Watershed. This study uses methods and data analysis based on the journal Kustratmoko, et al. (2002), by weighting 4 parameters of landslide vulnerability, namely slope, land use, soil erodibility and rainfall. There are 5 classes of vulnerability to landslides in the Bakar Sub-watershed, namely the safe class covering an area of 1,834.53 ha or 58.10% of the Bakar Sub-watershed, a moderately vulnerable class covering an area of 649.38 ha or 20.56% of the area of the Bakar Sub-watershed, a moderately vulnerable class covering an area of 666.60 ha or 21.11% of the area of the Bakar Sub-watershed, a vulnerable class covering an area of 6.81 ha or 0.21% of the area of the Bakar Sub-watershed, and a very vulnerable class of 0.12 ha or only 0.003% of the area Bakar sub-watershed. Validation of land use was carried out at 14 points of vulnerability to landslides, namely, 11 points of the vulnerability class changed due to changes in land use, based on the validation there were 2 points into the safe class, the moderately vulnerable class became 1 point, the moderately vulnerable class became 7 points, the vulnerable class became 2 point and for very vulnerable class to be 2 points.Tanah longsor adalah perpindahan material pembentuk lereng berupa batuan, bahan rombakan, tanah, atau material campuran tersebut, bergerak ke bawah atau keluar lereng. Penurunan daya dukung DAS menjadi salah satu faktor terjadinya tanah longsor, Tujuan penelitian ini adalah untuk menganalisis tingkat kerawanan longsor dan memvalidasi tingkat kerawanan longsor berdasarkan penggunaan lahan yang aktual di wilayah DAS Tabunio Sub DAS Bakar. Penelitian ini menggunakan metode dan analisis data berdasarkan jurnal Kustratmoko, et al. (2002), dengan melakukan pembobotan 4 parameter kerawanan longsor yaitu kemiringan lereng, penggunaan lahan, erodibilitas tanah dan curah hujan. Kerawanan longsor di Sub DAS Bakar terdapat 5 kelas kerawanan yaitu kelas aman seluas 1.834,53 ha atau 58,10 % dari Sub DAS Bakar, kelas agak rawan seluas   649,38 ha atau 20,56 % dari luas Sub DAS Bakar, kelas cukup rawan seluas 666,60 ha atau 21,11 % dari luas Sub DAS Bakar, kelas rawan seluas 6,81 ha atau 0,21 % dari luas Sub DAS Bakar, dan kelas sangat rawan seluas 0,12 ha atau hanya 0,003 % dari luasan area Sub DAS Bakar. Validasi penggunaan lahan yang dilakukan pada 14 titik kerawanan longsor yaitu, 11 titik kelas kerawanannya berubah dikarenakan perubahaan penggunaan lahannya, berdasarkan validasi terdapat 2 titik  ke dalam kelas aman, kelas agak rawan menjadi 1 titik, kelas cukup rawan menjadi 7 titik, kelas rawan menjadi 2 titik dan untuk kelas sangat rawan menjadi 2 titik.